Criminal Liability For Algorithmic Manipulation in The Dissemination of Information in The Digital Era - Hartomi; Muhamad Adystia Sunggara; Wijayono Hadi Sukrisno (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
The development of digital technology has encouraged the emergence of algorithmic manipulation as a new form of cybercrime that has a significant impact on the integrity of digital public spaces. Practices such as bot army, astroturfing, and algorithmic amplification show that algorithms are no longer just tools, but play an active role in expanding the impact of an action. The main problem of this study is related to the unclear construction of the subject of criminal law and the limits of liability in the context of criminal acts mediated by algorithmic systems. This study aims to analyze the construction of subject and criminal law accountability to algorithmic manipulation according to Indonesian positive law and formulate a more adaptive criminal liability model. The method used is normative legal research with legislative, conceptual, and comparative legal approaches. The results of the study show that the Criminal Code and the ITE Law have not been able to accommodate the complexity of the agency chain in the algorithmic system, thus creating an accountability gap. To address this, the study proposes a